PROFIL SENYAWA POLAR DAN SEMI POLAR DAUN TEMBELEKAN (LANTANA CAMARA) ASAL PULAU TIMOR - Kapitan, Origenes Boy Kapitan; Kusumawardhani, Dina T.; Nitti, Fidelis; Kedjo, Gervasia Y (Prodi Pendidikan Biologi FKIP Universitas Kristen Artha Wacana, 2024)
Tembelekan (Lantana camara) is a shrub widely distributed in tropical regions, including the island of Timor. The arid and semi-arid tropical climate of Timor is believed to accumulate specific active chemical compounds different from other regions. Tembelekan leaves are processed into crude drugs and extracted using ethanol and ethyl acetate solvents. The preparation of ethanol and ethyl acetate extracts is carried out through the maceration method. The active chemical components of the ethanol and ethyl acetate extracts are characterized using FTIR and GC-MS. FTIR results indicate that the majority of functional groups present are similar due to the polar nature of the extracted compounds, with only a few differing functional groups between the two plant leaf extracts. GC-MS analysis reveals that the active chemical compounds in the ethanol extract of tembelekan leaves include hexadecanoic acid, phytol, 9,12,15-octadecatrienoic acid, 4,4-dimethyl-3-(3-methyl-3-buten-1-yliden)-2-methylidenbicyclo[4.1.0]heptane, and retinol. The active chemical compounds in the ethyl acetate extract of tembelekan leaves include tetradecanoic acid, 9,12,15-octadecatrienoic acid, squalene, 4,4-dimethyl-3-(3-methyl-3-buten-1-yliden)-2-methylidenbicyclo[4.1.0]heptane, and tricyclo[4.3.0.0(7,9)non-3-ene,2,2,5,5,8,8-hexamethyl-(1.alpha.,6.beta.,7.alpha.,9.alpha.). Metabolite secondary analysis of the plant using GC-MS shows that compounds in L. camara are dominated by derivatives of plant fatty acids (lipids) as an adaptation to the growing environment.